Working at the interface of cultures eighteen lives in social science - Bond, Michael Harris 1944- (Routledge, 1997)
A collection of essays by leading cross cultural researchers who each relate their own personal experience of working with different cultures and examine the influence this has had on their way of thinking, working and perceiving the world.